Financial reporting under IFRS : A topic based approach - Dick, Wolfgang, 1965-; Missionier-Piera, Franck (New York : Wiley, 2010)
'This practical text on financial accounting and reporting offers a global perspective on IFRS. It presents the rationale and principles prescribed throughout the IAS/IFRS, including numerous examples from large international companies, and develops fundamental skills necessary to read and use the information contained in all financial statements. The first part of the book presents the structure of the balance sheet and income statement, their links, and the accounting mechanisms to prepare them. The second part analyzes how balance sheet items are identified evaluated, and then reported. The book concludes by examining the use of financial statements-the analysis of the firm's performance and its risks'--
Includes bibliographical references and index.
Keywords: Financial statements; Accounting -- Standards; International finance